El Excentrico, 1962-08-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 5, 1962 [5 de Agosto de 1962]. Ano 12, No 19. Cover has a photograph of Esther Martinez and Hugo Saenz in wedding attire. The headline reads, "The former Esther Martinez now Mrs. Hugo Saenz."